Multiple Organ‐Dysfunction Secondary to Multiple Bee Sting: A Case Report From Tanzania - Kelvin M. Musa; Auson Albert; Jane G. Zakaria; Ronald G. Mbwasi; Anorld David; Elton Meleki (Clinical Case Reports, 2026)
ABSTRACT An 8‐year‐old boy sustained over 200 bee stings, developing airway‐threatening facial oedema requiring intubation and ICU admission, with severe anemia (Hb 3.2 g/dL), rhabdomyolysis, intravascular haemolysis and marked hepatic injury (AST 2505 U/L), yet preserved renal function. He recovered without dialysis, extubated by Day 3 and discharged by Day 8.